Electric Power Generation Modeling for an Experimental Biomimetic Turbine with Permanent Magnets in Places with Low Water Flow in the Mantaro Valley-Perú - Camayo, K.J. (2021)
The paper presents a methodology for the design of propeller and generator of a biomimetic hydraulic turbine, as well as an estimate of the electrical power generated for places with low-flow water inflows in the Mantaro Valley, Junín - Perú. The objective was to model the power generated by the biomimetic turbine when it is installed in irrigation channels of 0.8 x 0.8 m2, as a proposal for a micro-hydroelectric plant, an alternative generation with renewable energy, where the flow is at least 4 m3/s. For the verification of the design, a simulator of real conditions such as Computational Fluid Dynamics was used to predict the capacity the amount of force that acts on the movement axis based on the Finite Element Method, to verify the structural unity of the design. The design methodology is based on biomimetic technology, continuity equations, Reynolds Averaged Navier-Stokes Equations, equations applied to determine power, through computational simulation of the turbine, obtaining data such as shaft speed and torque, through the percentage of pressure that exists in each hood, the power generated in the entire system was determined, by means of mathematical modeling a permanent magnet generator was developed as an alternative generator for this type of turbine.